2018
DOI: 10.1371/journal.pone.0203999
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the West African forest-savanna mosaic, insights from central Togo

Abstract: The West African forest-savanna mosaic, an important habitat for biodiversity and humans, is severely degraded, fragmented and modified by human activities. However, few studies have quantified the land cover changes observed over time and/or analysed the drivers of change. This study focused on Fazao-Malfakassa National Park, the largest in Togo, uses a combination of remote sensing, ground surveys and questionnaires to: (i) quantify vegetation changes, (ii) determine the drivers of change, (iii) compare resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 28 publications
1
64
0
3
Order By: Relevance
“…In an area as complex as ours, with small parcel sizes, the overall accuracies of 76.79% and 82.46% (less than the 85% target value) seem quite relevant for LULC change analysis [49,50]. In Togo, in similar contexts, accuracies of the same order of magnitude have been obtained by several studies [13,17,22]. Similar accuracies were also obtained on historical images of the Amazon [24].…”
Section: Lulc Mapping and Accuracysupporting
confidence: 72%
See 1 more Smart Citation
“…In an area as complex as ours, with small parcel sizes, the overall accuracies of 76.79% and 82.46% (less than the 85% target value) seem quite relevant for LULC change analysis [49,50]. In Togo, in similar contexts, accuracies of the same order of magnitude have been obtained by several studies [13,17,22]. Similar accuracies were also obtained on historical images of the Amazon [24].…”
Section: Lulc Mapping and Accuracysupporting
confidence: 72%
“…We chose the Sentinel 2 image for the last time point because of its availability and high spatial resolution (10 m). Studies showed the high potential of Sentinel 2 images for improving the monitoring of tropical forests and savannahs [22,23]. For the selected years, we favoured acquisitions from the late rainy season and early dry season to obtain the maximum contrast between the different elements of the landscape [24].…”
Section: Satellite Imagerymentioning
confidence: 99%
“…The results of Badjana et al (2017); Koglo et al (2018) revealed that deforestation and savanna changed to cropland and settlements in south and north of Togo. In Fazao-Malfacassa National Park, in the northern part of the MRB, Atsri et al (2018) found that forest and savanna are degraded, which could be explained by agriculture expansion, bush fire, timber extraction and linked by population growth. By assessing the land use change process in the Kéran protected area in the northern Togo, Polo-Polo-akpisso et al 2019confirmed that savanna and forest have decreased annually at the rate of more than 2%, whereas cropland and settlements have increased in the region.…”
Section: Accuracy Assessment and Past Land Cover Changementioning
confidence: 99%
“…LULC spatial trend direction and location are approximately situated in the locations of the main cities of the basin, therefore, LULC spatial trend can be explained by population activities and growth as mentioned by Koglo et al (2018) in the south district of MRB. Because of its fine resolution, the Nangbéto dam area and some protected forests such as Malafacassa (Amoussou et al, 2017;Atsri et al, 2018) are well delimited. The excellent reclassification of these land cover is due to low and high albedo factor of water and forest which plays a role during data collection by satellite's sensors.…”
Section: Land Use and Land Cover Scenarios Accuracy And Assessmentmentioning
confidence: 99%
See 1 more Smart Citation